Earthworm species in public parks in Curitiba, Paraná, Brazil - Ferreira, Talita; Santos, Alessandra; Demetrio, Wilian C.; Cardoso, Guilherme B.x.; Moraes, Rafael; Assis, Orlando; Niva, Cintia; Smokanit, Manoela; Knópik, Juliane; Sautter, Klaus D.; Brown, George G.; Bartz, Marie L.c. (Zootaxa, 2018)
Earthworms are important macroinvertebrates that provide soil ecosystem services and are also useful environmental bioindicators. Urban areas around the world have major impacts on biodiversity and the objective of the present study was to assess the role of urban parks of Curitiba, Paraná State, in preserving native earthworm species. Earthworm populations were sampled in five parks (Barigui, Tingui, Barreirinha, Passaúna and the Botanic Garden), in two land use systems (grass lawns and secondary forest fragments) in two seasons, summer (November 2013) and winter (June 2014). A total of twelve earthworm species were identified, belonging to six families: Glossoscolex sp.1, Fimoscolex sp.1, sp.2 and sp.3 (Glossoscolecidae), Pontoscolex corethrurus (Rhinodrilidae), Eukerria tucumana (Ocnerodrilidae), Amynthas gracilis, Amynthas corticis, Metaphire californica (Megascolecidae), Aporrectodea rosea and Lumbricus rubellus (Lumbricidae), the latter being the first record for this species in Brazil. In addition, a single unidentified juvenile Dichogaster sp. (Acanthodrilidae) was found. Four new species were found and three out of five urban parks of Curitiba (especially the Botanic Garden) were able to preserve native species, though their abundance was low and exotic species (n=8) predominated, attributed to human disturbance that favors invasion and colonization of exotic earthworms.